Nexus between social responsibilities of young cinematic celebrities and public recognition: Evidence from China - Zhao, Yun; Eyraud, Tina; Xue, Yaowen; Imran, Muhammad; Wang, Kai; Sun, Xiaotong (Frontiers in Psychology, 2022)
As public figures, cinematic celebrities’ behaviors have widespread influence on the whole society, and this also applies to China. Their influence is reflected in public recognition. This research classifies celebrity social responsibility as behavior within the law, professionalism, family ethics, public morality and charity. We selected 286 cinematic celebrities as study objects and obtained public recognition data through 2600 questionnaire surveys. The findings of the study indicate that there is a positive, linear relationship between cinematic celebrities’ social responsibility and public recognition. In particular, family ethics and public moral responsibility demonstrate a significant positive correlation with public recognition. However, there was no significant correlation found between lawful responsibility and public recognition. Finally, this paper makes additional suggestions and recommendations drawn from the data and reported in the conclusion.